Hyaluronic acid-coated Poly(L-lactide-co-1,3-trimethylene carbonate) modulate early cellular-scaffold interactions and osteogenic potential: a comprehensive in vitro and in vivo evaluation using mesenchymal stromal cells - Goksøyr, Øyvind; Yassin, Mohammed A.; Kivijärvi, Tove; Suliman, Salwa; Rosén, Annika; Finne-Wistrand, Anna; Mustafa, Kamal (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionSynthetic polymers are widely used in scaffold fabrication but are generally bioinert and hydrophobic, limiting cell adhesion and interaction. Hyaluronic acid (HA) is a ubiquitously expressed polycarbohydrate and a key extracellular matrix component that regulates tissue hydration, cell adhesion, motility, and regeneration. Incorporating HA into synthetic materials presents a promising strategy to enhance hydrophilicity and support biological functions, such as cell adhesion and osteogenic differentiation. This study investigated the effects of HA coating on the physicochemical characteristics and osteogenic potential of poly(L-lactide-co-1,3-trimethylene carbonate) (PLATMC) scaffolds.MethodsPLATMC scaffolds were coated with HA via immersion. HA stability during sterilization and culture was assessed alongside release kinetics. BMSC responses and osteogenic differentiation were evaluated in vitro and in vivo over six months. Scaffold wettability was analyzed to determine changes in surface hydrophilicity following HA coating.ResultsHA coating improved scaffold wettability in a concentration-dependent manner. HA release was characterized by burst kinetics, becoming undetectable after a few days under in vitro conditions, indicating that HA-driven effects are expected to be strongest during early cell–material interactions. In vitro, human BMSC showed RHAMM upregulation across all HA groups and CD44 upregulation in the 0.5% HA group after 24 hours. Rat BMSC exhibited increased osteocalcin expression, suggesting enhanced osteoinductive activity, corroborated by a trend toward osteopontin upregulation in human BMSC. In vivo, μCT analysis revealed higher tissue density surrounding HA-coated scaffolds at 8 weeks compared to 6 months in a rat subcutaneous implantation model.ConclusionHA coating improved scaffold hydrophilicity and promoted early cell adhesion and osteogenic signaling. The findings indicate that HA-coated PLATMC scaffolds support early cellular engagement and osteoconductivity, while long-term outcomes are likely governed by intrinsic scaffold properties. These results highlight the potential of HA-coated PLATMC scaffolds for biofabrication in dentistry, particularly in oral and maxillofacial bone regeneration.